Clocks in magmatic rocks - Costa, Fidel (2022)
Understanding the evolution and processes that shape our planet critically depends on the robustness of the absolute ages and process durations obtained from rocks and crystals. Two main aspects of time information on magmatic systems are currently at the forefront of new knowledge. The capacity to determine process durations on human timescales makes it possible to relate the magma dynamics below active volcanoes with the monitoring signals measured at the surface, thereby improving eruption hazards mitigation. The combination of precise in situ dating of accessory minerals and diffusion chronometry is unraveling the incremental growth of large silica-rich magma reservoirs over thousands to hundreds of thousands of years and illuminates the complex relationships between plutonic and volcanic systems. Further progress could be made by decreasing the volume of the analyzed crystals and the error of time determinations, addressing the crystal representativeness and sampling bias, and connecting the time information with physicochemical models of magmatic systems. squfensp Rock-forming minerals are time capsules of magmatic processes that occur on human timescales and can help to better anticipate volcanic eruptions. squfensp In situ dating of accessory minerals reveals that large magma reservoirs evolve through multiple thermal fluctuations of over tens to hundreds of thousands of years. squfensp Progress on conceptual models of magma storage and rejuvenation requires improved error analysis of timescales and representativeness of crystal populations.